HASIL BELAJAR KETERAMPILAN MENULIS BAHASA JERMAN DENGAN MENGGUNAKAN MEDIA KARTU PADA SISWA KELAS XI BAHASA MAN BANGKALAN - SYAFII, IMAM (LATERNE, 2016)
This study examines the outcomes of learning German language writing skills by using media card. Background based on the study of this study was to write one language skills be the goal of every teaching in schools. Based on interviews conducted with a German language teacher in MAN Bangkalan, learning writing skills became theproblem that so far, still have no exact solutin. So that, the media cardwas chosen as a learning resource to facilitate students in understanding the learning material and undergo the learning process. Formulation of the problem in this research is how the student learning outcomes by using media cards to practice the skills of writing German in class XI student of English MAN Bangkalan ?. While the purpose of this study was to describe the results of student learning using  media card in practising  the skills of writing German in class XI student of English MAN Bangkalan . This research was conducted as many as four meetings. Source of research data obtained from the test results of student learning in the form of Pre Test and Post Test. This research data of test results of the students then described and summarized. The results of research and discussion in getting the test results and learning outcomes of prior learning process using  media card and after the learning process using a media card , with the following description : Pre Test results showed there were 15 students from 36 students who take the learning is able to reach the KKM (Minimal Complete Criterion ). While the Post Test results showed there were 30 students from 33 students who take the learning is able to reach the KKM. Based on these results, it can be seen that there is an increase in student learning outcomes prior to the learning process using a media card and after the learning process using a media card in the German language writing skills. From the results of these studies indicate that media cards can be used by teachers as a   perfect learning media for German writing skills .   Keywords : media cards , learning outcomes , writing skills